Kinetics of Biomarkers of Oxidative Stress in Septic Shock: A Pilot Study - Martin Helan; Jan Malaska; Josef Tomandl; Jiri Jarkovsky; Katerina Helanova; Klara Benesova; Michal Sitina; Milan Dastych; Tomas Ondrus; Monika Pavkova Goldbergova; Roman Gal; Petr Lokaj; et al. (MDPI AG, 2022)
Septic shock is a major cause of mortality in ICU patients, its pathophysiology is complex and not properly understood. Oxidative stress seems to be one of the most important mechanisms of shock progression to multiple organ failure. In the present pilot study, we have analysed eight oxidative-stress-related biomarkers in seven consecutive time points (i.e., the first seven days) in 21 septic shock patients admitted to the ICU. Our objective was to describe the kinetics of four biomarkers related to pro-oxidative processes (nitrite/nitrate, malondialdehyde, 8-oxo-2'-deoxyguanosine, soluble endoglin) compared to four biomarkers of antioxidant processes (the ferric reducing ability of plasma, superoxide dismutase, asymmetric dimethylarginine, mid-regional pro-adrenomedullin) and four inflammatory biomarkers (CRP, IL-6, IL-10 and neopterin). Furthermore, we analysed each biomarker's ability to predict mortality at the time of admission and 12 h after admission. Although a small number of study subjects were recruited, we have identified four promising molecules for further investigation: soluble endoglin, superoxide dismutase, asymmetric dimethylarginine and neopterin.